Unlocking Corporate Value: How Integrated Reporting, Profitability, and External Financing Interact in Shaping Company Influence - Esmawati; Aryani Intan Endah Rahmawati (Universitas Negeri Semarang, 2024)
Purpose: Fluctuations in share prices in the capital market are related to company value, where when share prices fall, many shareholders tend to sell their shares to minimize losses. This can decrease the company’s internal capital due to the loss of investors and creditors. As a result, companies may need to rely on external capital such as loans to meet long-term capital needs. The company’s ability to return external capital can be analyzed through integrated reports and profitability. This research analyzes the effect of integrated reporting and profitability on company value which is moderated by external financing. Method: Population in all financial sectors listed on the Indonesia Stock Exchange (BEI) in 2018-2022 and a sample of 51 companies was obtained. The moderation analysis technique uses Moderated Regression Analysis to test the hypothesis using Eviews 10. Findings: The research results show that integrated reporting has a significant positive effect on company value and is moderated by external financing. Profitability has a significant negative effect on company value but cannot be moderated by external financing. Novelty: The research can contribute to the development of accounting science and theory, especially IR disclosure in developing countries with a voluntary system such as Indonesia. This research also contributes to financial practitioners using IR in making investment decisions.